2017
DOI: 10.3233/wor-172514
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Safety and Health professionals’ work ability concept perception, and comprehension of regulations

Abstract: There are significant comprehension disparities in the understanding of the concept of work ability. Correct understanding of the concepts and constructs in a given regulatory framework are tantamount to the proper implementation of the requirements of the regulation provisions. There is a need to streamline and improve the understanding of OSH professionals in order to ensure uniformity of purpose, and hence fulfilment of the vision of the regulation in focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…This study found that it is crucial to evaluate nurses’ work ability and professional competence (including age, years of service and expertise) for shift and team arrangement. Work ability is defined as an individual's ability to perform tasks and to meet the required skill and competency levels at work (Suleiman, 2017). Making these evaluations in a timely manner would allow low seniority nurses to benefit from the support of more experienced colleagues and feel less pressure in caring for patients, while high seniority nurses could assist in their areas of professional expertise, where they can be most useful.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that it is crucial to evaluate nurses’ work ability and professional competence (including age, years of service and expertise) for shift and team arrangement. Work ability is defined as an individual's ability to perform tasks and to meet the required skill and competency levels at work (Suleiman, 2017). Making these evaluations in a timely manner would allow low seniority nurses to benefit from the support of more experienced colleagues and feel less pressure in caring for patients, while high seniority nurses could assist in their areas of professional expertise, where they can be most useful.…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados encontrados, como versan las fuentes 23,27,29 , dependen del grupo en el que se realizan las evaluaciones. En nuestro estudio, la mayor proporción de trabajadores fue representada por personal de enfermería, tanto Auxiliares de Enfermería (46%) como Enfermeras (41%), así que los factores que podrían influenciar en los niveles ICT que encontramos, podrían estar condicionados por las percepciones de estos grupos laborales.…”
Section: Caridad León Roblesunclassified